Without bread and without roses: from the Marxist feminism inspired by May 1968 to the academicism of gender - Gonçalves, Renata (Pontifícia Universidade Católica de São Paulo, 2009)
In this article we reexamine the dynamics of the feminist movement, highlighting the particularity of its two faces in Brazil: on the one hand, a “revisited” feminism and on the other, the women’s movement. If at the beginning we find a combative feminism in the model of the explosion of May 1968, today we perceive a feminism increasingly confined to academic study and/or institutionalized, especially through the provision of advice to NGO’s, which contributes to the reflux of the class struggle.